DEVELOPMENT OF FLIPBOOK-INTERACTIVE MODULES: IMPROVING UNDERSTANDING OF BASIC ELECTRICAL CONCEPTS - Haryudo, Subuh Isnur; Fransisca, Yulia; Suryaman, Heri; Adha, Hanif Rifai (Universitas Labuhanbatu, 2025)
Purpose – This research aims to develop an interactive e-module based on Flipbook to improve the conceptual understanding of basic electricity Methodology – The methodological approach in this study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The methods used include needs analysis, design, and evaluation, with a focus on improving student interactivity and learning outcomes through the use of an attractive Flipbook application. The sample of this study is 80 students of Electrical Engineering Education, State University of Surabaya, who were obtained through purposive sampling techniques. The data collection procedure is in the form of a questionnaire to find out the response of validators and students to the interactive e-module, and provides multiple-choice questions to measure learning outcomes.Findings – The results of the study showed that the flipbook-based e-modules developed had very high validity, with assessments from subject matter experts and media experts achieving an average score of 88.7%, with a very valid category. In addition, this e-module has also proven to be practical and effective in improving students' understanding of basic electrical concepts. The results of the assessment of student responses in the large group trial obtained an average percentage of 90% in the practical category. The results of the trial showed an increase in student learning outcomes, with an average of 82.6 in the effective category.Contribution – This research makes a significant contribution to the development of learning media that is in accordance with the current development of educational technology. The use of this e-module can increase students' interest and motivation to learn, as well as provide alternative learning media that are more interesting and interactive.